Early neonatal presentation of methylmalonic aciduria: a case report from rural central India - Sneha Barahate; Anuragsingh Chandel; Kolhe, Swapnil; Varsha Chauhan; Manish Jain (International Journal of Contemporary Pediatrics, 2023)
Methylmalonic aciduria (MMA) is an inborn error of metabolism that results in accumulation of methylmalonic acid in blood and increased excretion in urine. They are characterized by impaired conversion of methymalonyl CoA to succinyl CoA by the enzyme methylmalonyl CoA mutase resulting in accumulation of metabolites of branched chain amino acid catabolism. MMA has a wide clinical spectrum, ranging from a benign condition to fatal neonatal disease. Its onset ranges from the neonatal period to adulthood. We report a case of a day 4 old male child who presented with the complaints of respiratory distress, poor feeding, and excessive crying. Mother had a history of previous neonatal loss on day 3 of life. Diagnosis of MMA was made with the help of clinical presentation and laboratory investigations. At present universal newborn screening for metabolic disorders is not done routinely in India. Diagnosing and managing IEM in India and other developing countries is a challenge since most of the classic metabolic test are not routinely available. Many cases are asymptomatic and undetected and hence we report this case to stress the importance of including MMA in newborn screening programme for early detection and intervention.